2016
DOI: 10.3866/pku.whxb201605121
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nanoporous CoFe<sub>2</sub>O<sub>4</sub> and Its Catalytic Performance during the Thermal Decomposition of Ammonium Perchlorate

Abstract: 摘要:采用胶晶模板法制备出具有三维多孔结构的纳米 CoFe2O4。利用 X 射线衍射仪(XRD)、傅里叶变换红 外(FT-IR)光谱仪、扫描电镜(SEM)、透射电镜(TEM)和 N2吸附-脱附对样品的晶型和形貌结构等进行表征, 采用差示扫描量热法(DSC)对比研究多孔纳米 CoFe2O4和球形纳米 CoFe2O4对高氯酸铵(AP)的热分解性能的 影响,并考察这两种催化剂对 AP 催化热分解的动力学参数。结果显示,制备出的多孔纳米 CoFe2O4样品具 有典型的尖晶石结构,孔径约 200 nm;比表面积明显高于 40 nm 球形 CoFe2O4,达到 55.646 m 2 •g -1 。DSC 测试结果表明:多孔纳米 CoFe2O4的加入促进了 AP 的热分解,最高使 AP 的高温分解峰温降低 91.46°C,能

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Besides, bimetallic oxide usually owns better catalytic activity for thermal decomposition of oxidants . Several kinds of bimetallic iron oxides have been fabricated and used for thermal decomposition of AP . These studies confirmed the catalytic activity of the ferrates for thermal decomposition of AP, however, most of the studies involved only single ferrate.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Besides, bimetallic oxide usually owns better catalytic activity for thermal decomposition of oxidants . Several kinds of bimetallic iron oxides have been fabricated and used for thermal decomposition of AP . These studies confirmed the catalytic activity of the ferrates for thermal decomposition of AP, however, most of the studies involved only single ferrate.…”
Section: Introductionmentioning
confidence: 74%
“…Besides, the catalytic activity of ferrate is also related to its crystallite size and particle size. The smaller crystallite size and particle size of NiFe 2 O 4 and CoFe 2 O 4 can provide more lattice defects and activity sites for AP thermal decomposition . The excellent catalytic activity of CoFe 2 O 4 comes from the synergistic interaction between Fe and Co, which is the most important factor affecting its catalytic performance for AP thermal decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…For pure AP, the calculation result of the activation energy for the HTD process is 151.5 kJ/mol, which is consistent with the reported value. [ 42 ] The E a of AP thermal decomposition by Cu‐CA‐3.5 is reduced by 105.8 kJ/mol. In general, the E a of AP decomposition is associated with the primary dissociation step.…”
Section: Resultsmentioning
confidence: 99%
“…The DSC curves of AP and RDX with and without catalysts at heating rates of 5, 10, 15, and 20 °C min –1 are shown in Figures S19 and S20, respectively. The kinetic parameters of the thermal degradation process were calculated according to the Kissinger method [ln­(β/ T p 2 ) = − E a / RT p + ln­(AR/ E a )], where β denotes the heating rate, T p represents the HTD peak temperature, R denotes the ideal gas constant, E a represents the apparent activation energy, and A denotes the prefactor of the Arrhenius equation . The value of E a can be calculated from the slope of the straight lines shown in Figure ; the computed results are displayed in Table S12.…”
Section: Resultsmentioning
confidence: 99%